(untitled) (SCIENCE TIME JOURNAL, 2026)
The present study investigates the theoretical foundations of neologisms in contemporary English and examines their implications for translation practice within the framework of linguistic innovation. The research combines theoretical analysis of word-formation processes with corpus-informed examination of recent lexical developments in order to identify patterns of neologism formation and the challenges they pose in translation. The study demonstrates that modern English neologisms primarily arise through compounding, blending, derivation, conversion, and semantic extension, processes largely driven by technological progress and digital communication. The findings further indicate that translators frequently encounter difficulties when equivalent terms do not exist in the target language, particularly in cases involving culturally specific or rapidly evolving concepts. Common translation strategies include borrowing, calque formation, descriptive translation, and functional equivalence, with the choice depending on communicative context and audience familiarity. The analysis also shows that many neologisms remain unstable or context-dependent, requiring flexible translation solutions. By connecting linguistic theory with translation methodology, the study contributes to understanding how lexical innovation influences intercultural communication. The results underline the importance of combining theoretical linguistic insight with practical translation strategies to ensure clarity and communicative effectiveness in the transfer of new lexical items across languages in rapidly changing communicative environments.